The Effect of Multi- Months Scripting on Health Care Workers’ Performance at HIV/AIDS Outpatient Clinics in Nairobi County, Kenya - Waithaka, Peter; Tenambergen, Wanja; Mwangi, Muthoni (International Journal of Professional Practice, 2025)
Healthcare workers (HCWs) shortage is a challenge facing health systems managers worldwide. The World Health Organization (WHO) projects a shortfall of 10 million HCWs by 2030, mostly in low-income countries. The shortage leads to high workload, poor HCW performance and undesirable patient outcomes. Implementation of Multi-Months Scripting (MMS) WHO guidelines reduces patient load in HIV/AIDS outpatient clinics. The study aims to demonstrate to policymakers, Health Systems Managers (HSMs), HCWs, and stakeholders that implementation of MMS results in improved HCWs performance. The study established the effects of MMS implementation on HCW’s performance. This was a descriptive cross-sectional study through self-administered questionnaire applied to 128 HCWs sampled through Multi-stage sampling, in 20 clinics. Descriptive, bivariate, and ordinal logistic regression analysis was done. The findings indicated that 56% of respondents were females, 89% had served for 6-15 years, 99% were aware of MMS guidelines, 98% received supportive supervision and 90% received training on MMS. Majority, 94 % agreed MMS clients were compliant and had high retention. However, 48 % sited HIV commodities stock-out 6 months prior to the study, 98% observed reduction in HIV clients due to MMS, reduced waiting time, and improved performance; while 93% had more time with clients. Bivariate analysis revealed significant correlation between HCW performance and MMS guidelines awareness (0.334), client compliance (0.225); and a weak correlation (-0.599) with capacity development. There was no significant correlation (0.041) between MMS commodities flow and HCW performance. Ordinal logistic regression revealed the most significant influencer of HCW performance was client compliance, MMS guidelines awareness, and HCWs capacity development in that order (Sig.002, .011, and .014 respectively). The study concluded that implementation of MMS guidelines resulted in improved HCWs performance. It recommends policymakers, HSMs, HCW and stakeholders to revise service delivery guidelines to accommodate MMS implementation for improved HCW performance and patient outcomes.